Determinants of the continuous use of E-GOV information systems and services in Morocco : Proposing an integrative model - SAGHIR , Zakaria; NAFZAOUI, Mohamed Achraf (Revue du contrôle, de la comptabilité et de l’audit, 2023)
The digital transformation of public administration is a strategic project that has been initiated by Morocco several years ago. It is a very ambitious project that is of great importance for the development and growth of the country. Yet, its success depends highly on the involvement and participation of citizens. However, in Morocco, there is a lack of comprehensive information regarding the adoption and usage of these solutions, as well as the e-gov satisfaction levels among citizens. This research aligns with theories of information system usage behavior in a post-adoption context and focuses on the user's perspective, emphasizing the importance of studying the peculiarities of their usage behavior in order to promote the success of the systems and solutions offered to them. After addressing the situation of e-gov services in Morocco and presenting the theoretical basis of the research, this article proposes, in its third part, an integrative model composed of a fusion between several theories with the objective to study the continuous use behavior of e-gov services and systems in Morocco. This model includes motivation and satisfaction constructs to explain usage continuance. The proposed model will be the starting point of an empirical study whose goal is to explore all the assumed relationships in the model and to analyze them.